Horses, Hemiones, Hydruntines? Assessing the Reliability of Dental Criteria for Assigning Species to Southwest Asian Equid Remains. (16th May 2016) - Twiss, K. C.; Wolfhagen, J.; Madgwick, R.; Foster, H.; Demirergi, G. A.; Russell, N.; Everhart, J. L.; Pearson, J.; Mulville, J.
Abstract: Many faunal assemblages across southwest Asia contain the remains of multiple wild equid species, which may reflect individual prehistoric human populations' use of different hunting and/or landscape exploitation strategies. Accurate equid species assignments are therefore important. This paper tests the extent to which zooarchaeologists agree on equid species assignments made using commonly used zooarchaeological dental identification criteria. Seven zooarchaeologists individually use published criteria to assign species to equid teeth from Neolithic Çatalhöyük in central Anatolia, then use Fleiss' kappa to measure our reliability of agreement. We assess our degrees of agreement for species assignments made using scanned images versus actual specimens and for mandibular teeth versus maxillary teeth. Having failed to achieve significant agreement, we conclude that zooarchaeologists should be cautious about species assignments made using these methods. Copyright © 2016 John Wiley & Sons, Ltd.